The Cerebral Arterial System: A Visual Recall Device - Patrick Sylvester; Douglas J. Gould; Lisa M.J. Lee (Association of American Medical Colleges, 2013)
Abstract Cerebral arterial anatomy is traditionally a complicated subject, commonly requiring visual aids in addition to gross dissection in a small and confined space. Thus, students often have a difficult time mastering the content. Furthermore, there are a limited amount of ancillary resources with images and or diagrams to help students learn the material with efficiency. To that end, a 16-slide PDF file containing diagrams and images of the cerebral arterial system was created for use by faculty, students, and residents in medicine and allied health field as a concise yet comprehensive review. By simplifying the Circle of Willis anatomy using diagrams, step-by-step diagrams of stick figures, and circles in which each subsequent diagram builds on the preceding, students and instructors can easily memorize the necessary content and comprehend the anatomical relationship of the important structures. This diagrammatic and step-wise construction is a well-known method for mastery of difficult topics. Transposition of the diagrams on to the real cadaveric images as presented in this module then applies the simplified content to the actual structures of the brain. Depending on the user, the presentation should take approximately 30-60 minutes to go through. Users are encouraged to go through each slide in sequence to utilize the resource most effectively for a simplified overview/review of cranial nerve anatomy. Instructors are recommended to use the resource as a formal or informal course content to provide a concise overview of cerebral arterial anatomy. The resource is also an ideal ancillary learning and review tool that may be used outside of class. Additionally, all original images and diagrams provided in the PDF file may be adapted for use in a variety of educational settings to increase discussion or instructional efficiency, and to foster a comprehensive review.